Introducing an Endocrine Laboratory (Journal of Pathology of Nepal, 2018)
The growing sub-specialty in Medical practice is beneficial for the patient as well as for the healthcare providers. Laboratory Medicine is also an emerging field to address the complexity of health arena. In earlier days, all laboratory investigations were performed in the single laboratory equipped with all sorts of machines and manpower. But the scenario has changed now with laboratories being specific for subject like Biochemistry, Hematology, Microbiology, Immunology, Genetics and many more. These specifications have proven that by doing so, there is better patient care and involvement of health personnel in various research activities, which ultimately helps in identification of cost effective laboratory approach of diseases.